Dificuldades na institucionalização da Nova Lei de Licitações e Contratos Administrativos: estudo de caso em um órgão público do Estado do Amazonas - Bastos, Yasmin da Rocha (Brasil, 2024)
This article aimed to identify the difficulties faced by a Public Body in the State of Amazonas for the institutionalization of the New Law on Tenders and Administrative Contracts, Law nº 14,133/2021. For successful institutionalization, the public sector must focus its efforts and resources on improving contract management to ensure that the new standard is effectively implemented. Achieving the desired result requires a complex effort to change legislation, control and management measures, as well as cultural and organizational aspects. To carry out this study, data were collected using the case study method, with a qualitative approach, through interviews carried out with five public agents from the Agency under study. As the main difficulty, the lack of publication of regulations deserves mention, the purpose of which is understood as a guideline and security for public agents to start bidding processes with the new legislation, in addition to difficulties in the cultural aspect, in which there is still resistance to changes in the face of the transition of federal laws. The study was limited to a Public Body in the State of Amazonas, and can be widely applied to other federal, state and municipal public bodies, at the national level, analyzing the institutionalization and post-institutionalization of the New Law on Tenders and Administrative Contracts.